Fiber-reinforced composite environment-friendly building template and preparation method thereof

By activating rice husks and straw and combining them with aerogel powder and composite flame retardant particles, polypropylene and crosslinking enhancer are used for bonding, the problems of insufficient mechanical properties, thermal insulation and flame retardant properties of building formwork are solved. , realize high-performance building formwork preparation, reducing environmental pollution and resource waste.

CN119161664AActive Publication Date: 2024-12-20JIANGSU LONGYUAN DECORATION MATERIAL CO LTD

Patent Information

Application Number
CN202411633930.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2024-12-20
Estimated Expiration
2044-11-15

AI Technical Summary

Technical Problem

The existing fiber-reinforced composite building formwork has shortcomings in terms of mechanical properties, thermal insulation and flame retardant properties, and the production process of traditional materials has a negative impact on the environment.

Method used

Using rice husks and straw as raw materials, modifying fibers are prepared by activation and surface modification, and combined with aerogel powder and composite flame retardant particles, polypropylene and crosslinking enhancers are used as binders, and intermolecular promotion is promoted through initiators. Cross-link bonding to form high-performance building formwork.

Benefits of technology

It significantly improves the mechanical properties, thermal insulation and flame retardant properties of building forms, while reducing environmental pollution and resource waste, which is in line with the concept of green buildings and sustainable development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a fiber-reinforced composite environment-friendly building template and a preparation method thereof, belongs to the technical field of building template processing, and is used for solving the technical problem that in the prior art, the mechanical property, the thermal insulation property and the flame retardant property of a fiber-reinforced composite building template need to be further improved. According to the invention, the rice hulls and the straws are recycled as reinforcing fibers, so that environmental pollution and resource waste can be reduced, the concept of green building and sustainable development is met, the aerogel micro powder and the composite flame-retardant particles are used as reinforcing materials to reinforce the modified fibers, and the polypropylene and the crosslinking reinforcing agent are used as organic adhesives, so that the composite flame-retardant composite fiber is prepared. And under the action of the initiator, crosslinking bonding of molecular bonds among molecules of the building template is promoted, so that the overall mechanical performance of the building template is improved, and meanwhile, the heat preservation and heat insulation performance, the flame retardant property, the water resistance and the alkali resistance of the building template material are further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building template processing, and in particular to a fiber-reinforced composite environmentally friendly building template and a preparation method thereof. Background Art

[0002] Building formwork is a temporary supporting structure, which is made according to the design requirements to shape the concrete structure and components according to the specified position and geometric dimensions, and bear the self-weight of the building formwork and the external loads acting on it. Traditional building formwork is mainly made of wood, steel and other materials. Although wood formwork has certain strength and machinability, due to the long growth cycle of wood, the large-scale use of wood can easily lead to excessive logging of forest resources and damage the environment. Steel formwork has higher strength and durability, but it is heavy and inconvenient to carry and install. At the same time, the production process of steel has high energy consumption, which also has a certain impact on the environment.

[0003] With the global attention paid to green buildings and sustainable development, building formwork, as an important auxiliary material in construction, has increasingly higher performance requirements in terms of environmental protection, mechanical strength, durability and other aspects. Traditional building formwork, such as wood formwork, has problems such as high resource consumption, easy damage and environmental pollution. New environmentally friendly materials such as rice husks and straw have gradually attracted attention and been applied to the preparation of building formwork due to their rich renewable resources and unique physical and chemical properties.

[0004] Rice husks and straws, as agricultural waste, have the advantages of high yield, low cost and renewability. In recent years, scientific researchers have made significant progress in converting fiber materials such as rice husks and straws into high-performance composite materials for the preparation of building formworks through technological innovation. However, rice husks and straws are composed of a highly absorbent epidermis and an inner shell with relatively low water absorption. They have strong water absorption and are not alkali-resistant. As a result, the building formworks made from them are prone to absorb water and deform during construction. The mechanical stability of the building formworks is poor. Traditional fiber-reinforced building formworks are usually cast by directly mixing the fibers with the resin. The cross-linking degree between the components of the building formworks is poor, and the mechanical strength of the building formworks needs to be further improved. In addition, the thermal insulation and flame retardant properties of the existing composite building formwork materials also need to be improved. Summary of the invention

[0005] The purpose of the present invention is to provide a fiber-reinforced composite environmentally friendly building formwork and a preparation method thereof, so as to solve the technical problem that the mechanical properties, thermal insulation properties and flame retardant properties of the fiber-reinforced composite building formwork in the prior art need to be further improved.

[0006] The object of the present invention can be achieved by the following technical scheme: a fiber-reinforced composite environmentally friendly building formwork, comprising the following components in parts by weight: 80-100 parts of polypropylene, 20-30 parts of a cross-linking reinforcing agent, 30-50 parts of aerogel micropowder, 80-100 parts of modified fiber, 30-40 parts of composite flame retardant particles, 2-3 parts of an initiator and 4-6 parts of an auxiliary additive; The cross-linking enhancer is obtained by processing the following steps: A1, adding 4-aminobenzenethiol, anhydrous ethanol and formaldehyde solution into a reaction kettle and stirring, raising the temperature of the reaction kettle to 60-70°C, keeping the temperature for reaction for 6-8h, and post-treating to obtain triphenylthiophenol triazine; The synthetic reaction formula of triphenylthiophenol triazine is:

[0007] The synthetic reaction principle of triphenylthiophenol triazine is: Under heating conditions, the aldehyde group of formaldehyde undergoes a nucleophilic substitution reaction with the amino group on 4-aminobenzenethiol. As the reaction proceeds, the product further cyclizes to form a triazine structure, and triphenylthiophenol triazine with triphenylthiophenol modified triazine is prepared. The mass spectrometry analysis data are: m / z: 411.0898 (100.0%), 412.0931 (22.7%), 413.0856 (13.6%), 414.0889 (3.1%), 413.0965 (2.5%), 412.0891 (2.4%), 412.0868 (1.1%).

[0008] A2. Add triphenylthiophenol triazine, isophorone diisocyanate and toluene into a nitrogen-protected reactor and stir. The temperature of the reactor is raised to 50-60° C., a catalyst is added into the reactor, and the reaction is kept warm for 3-4 hours. Add 5-methyl-2-(1-methylvinyl)-4-hexen-1-ol into the reactor, and the reaction is kept warm for 4-5 hours. Post-treatment is performed to obtain a cross-linking enhancer.

[0009] The synthetic reaction formula of the cross-linking enhancer is:

[0010]

[0011] Where:

[0012] The synthetic reaction principle of the cross-linking enhancer is: The thiol group on triphenylthiophenol triazine undergoes a condensation reaction with the isocyanate group on isophorone diisocyanate, and an intermediate with isocyanate end-capping modification is prepared by controlling the dosage ratio of reactants and utilizing the difference in the reactivity of two isocyanate groups on isophorone diisocyanate. The isocyanate group on the intermediate further undergoes condensation with the alcohol hydroxyl group on 5-methyl-2-(1-methylvinyl)-4-hexene-1-ol, so as to prepare a cross-linking enhancer with polyunsaturated olefin double bond modification.

[0013] Furthermore, the initiator is benzoyl peroxide, the auxiliary additives are composed of an antioxidant, a dispersant, a flame retardant and a plasticizer in a weight ratio of 1:2:3:2, the antioxidant is one or more of antioxidant 168, antioxidant 1010, and antioxidant 1076, the dispersant is one or more of sodium stearate, calcium stearate, zinc stearate, and magnesium stearate, the flame retardant is one or more of tributyl phosphate, tri(2-ethylhexyl) phosphate, tri(2-chloroethyl) phosphate, tri(2,3-dichloropropyl) phosphate, and tri(2,3-dibromopropyl) phosphate, and the plasticizer is a phthalate.

[0014] Furthermore, in step A1, the amount ratio of 4-aminothiophenol, anhydrous ethanol and formaldehyde solution is 1g:6mL:3-5g, the mass fraction of the formaldehyde solution is 30-37%, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is kept at 60-70°C, the solvent is evaporated under reduced pressure, dichloromethane and purified water are added to the reactor, stirred for 20-30min, allowed to stand for separation, the organic phase is dried with anhydrous magnesium sulfate for 40-60min and then transferred to a rotary evaporator with a water bath temperature of 40-50°C, Dichloromethane is distilled off under reduced pressure to obtain triphenylthiophenol triazine; in step A2, the molar ratio of triphenylthiophenol triazine, isophorone diisocyanate and 5-methyl-2-(1-methylvinyl)-4-hexene-1-ol is 1:3:3, the amount ratio of isophorone diisocyanate, toluene and catalyst is 1g:5mL:0.01g, the catalyst is dibutyltin diacetate, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is increased to 70-80°C, and toluene is distilled off under reduced pressure to obtain a cross-linking enhancer.

[0015] Furthermore, the preparation method of the aerogel powder is as follows: adding aluminum sec-butoxide and isopropanol to a reactor and stirring until the system is dissolved, raising the temperature of the reactor to 70-80°C, adding dilute nitric acid to the reactor, keeping the temperature for reaction for 2-3 hours, adding ethyl orthosilicate and allyl triethoxysilane to the reactor, keeping the temperature for reaction for 2-3 hours, standing and aging for 8-10 hours, and post-treating to obtain aerogel powder.

[0016] The synthesis reaction principle of aerogel powder is: After aluminum sec-butoxide is dissolved in isopropanol solvent, it undergoes hydrolysis reaction with the addition of dilute nitric acid to generate aluminum hydroxide and sec-butanol. The hydrolysis product will further undergo condensation reaction to form small colloidal particles bonded by aluminum oxygen bonds. These small particles gradually grow and cross-link to form a gel with a three-dimensional network structure. Ethyl orthosilicate and allyl triethoxysilane are added to the reaction system as silicon sources. They will also undergo hydrolysis and condensation reaction to generate colloidal particles bonded by silicon oxygen bonds. The hydrolysis product of the silicon source is further cross-linked with the hydrolysis product of the aluminum source to form an aluminum oxide-silicon oxide composite gel network. After solidification, it is washed and dried to prepare aluminum / silicon composite aerogel micropowder.

[0017] Furthermore, the dosage ratio of the aluminum sec-butoxide, isopropanol, dilute nitric acid, ethyl orthosilicate and allyl triethoxysilane is 3-5g:30-50mL:5-7mL:8-10g:2-3g, the concentration of the dilute nitric acid is 0.8-1.3mol / L, and the post-treatment comprises: after the reaction is completed, the temperature of the reactor is kept at 70-80°C, the solvent is evaporated under reduced pressure, the temperature of the reactor is lowered to room temperature, anhydrous ethanol is added to the reactor, stirred and dispersed for 50-60min, allowed to stand, the supernatant is separated, the lower solid is centrifuged and dried, and then transferred to a drying oven at a temperature of 60-70°C, and dried to constant weight to obtain aerogel powder.

[0018] Furthermore, the modified fiber is obtained by processing the following steps: B1. Add rice husk and rice straw into a grinder and grind into fiber powder with a particle size of 5-8 mm; B2, adding fiber powder and activation solution into the reactor and stirring, raising the temperature of the reactor to 70-80°C, keeping the temperature for reaction for 2-3h, and post-treating to obtain pretreated fiber; B3. Add the pretreated fiber, anhydrous ethanol and KH-570 into the reactor and stir for 20-30 minutes. Add 5wt% sodium hydroxide solution into the reactor, increase the temperature of the reactor to 50-60°C, keep the temperature for 3-4 hours, and obtain the modified fiber after post-treatment.

[0019] The synthetic reaction principle of modified fiber is: By crushing natural fibers such as rice husks and straw through a grinder to increase their surface area, and pre-treating the fiber powder with an activation liquid, the crystal structure of cellulose can be destroyed, the accessibility and reactivity of the fiber can be improved, and favorable conditions for subsequent surface modification can be created; based on the pretreatment, the fiber surface is modified using KH-570 under alkaline conditions to form stable chemical bonds on the fiber surface, thereby introducing organic functional groups into the fiber surface to prepare modified fibers.

[0020] Furthermore, in step B2, the fiber powder and the activation solution are used in a ratio of 1g:10-15mL, and the activation solution is composed of potassium hydroxide, urea, sodium dodecyl sulfate, 10wt% hydrogen peroxide and purified water in a ratio of 5g:2g:1g:30g:60mL. The post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, the filter cake is washed with purified water until it is neutral and then dried, and the filter cake is transferred to a drying oven at a temperature of 60-70°C, dried to constant weight, and pretreated fiber is obtained; in step B3, the pretreated fiber, anhydrous ethanol, KH-570 and 5wt% sodium hydroxide solution are used in a ratio of 5g:50mL:2-3g:10mL. The post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, the filter cake is washed with purified water until it is neutral and then dried, and the filter cake is transferred to a drying oven at a temperature of 60-70°C, dried to constant weight, and modified fiber is obtained.

[0021] Furthermore, the composite flame retardant particles are processed by the following steps: C1. Place diatomaceous earth in a muffle furnace, raise the temperature of the muffle furnace to 450-500°C, keep the temperature for 3-4 hours, and naturally cool it to room temperature to obtain a calcined powder; C2, adding the calcined powder and phosphoric acid solution into the reactor and stirring, raising the temperature of the reactor to 70-80°C, keeping warm and stirring for 30-40 minutes, adding urea solution into the reactor, raising the temperature of the reactor to reflux the system, keeping warm and reacting for 60-80 minutes, adding the modification liquid into the reactor, and post-treating to obtain the crude composite flame retardant particles; C3. Transfer the crude composite flame-retardant particles to a ball mill, set the speed of the ball mill to 200-250 r / min, and ball mill for 30-40 minutes to obtain composite flame-retardant particles.

[0022] The synthetic reaction principle of composite flame retardant particles is: During the high-temperature roasting process of diatomite, organic impurities, moisture and volatile substances in the diatomite can be removed, the mineral phase change and structural rearrangement in the diatomite can be triggered, the physical and chemical properties of the diatomite can be changed, the specific surface area, pore structure, surface energy, etc. of the diatomite can be improved, and phosphoric acid can be more easily penetrated into the interior of the diatomite and form phosphates with aluminum, urea and other substances, forming an interlaced loading effect in the diatomite. Under an acidic environment, the siloxane bonds in the modification liquid are hydrolyzed and react with the active groups on the surface of the particles, and a fluorine-containing segment and an olefin-modified polysiloxane coating are formed on the outside of the particles. After ball milling and mixing in a ball mill, the crude composite flame-retardant particles are impacted and rubbed by the high-speed rotating sphere, and are gradually broken into smaller particles, which promotes mixing and uniform distribution between the particles, and prepares composite flame-retardant particles.

[0023] Furthermore, in step C2, the amount ratio of the calcined powder, the phosphoric acid solution, the urea solution and the modifying solution is 10g:20mL:10mL:5g, the concentration of the phosphoric acid solution is 1.5mol / L, the concentration of the urea is 3.2mol / L, and the modifying solution is composed of tridecafluorooctyltrimethoxysilane and allyltriethoxysilane in a weight ratio of 2:1. The post-treatment includes: after the reaction is completed, the reactor is kept warm and refluxed, and the solution is evaporated under reduced pressure to obtain a crude composite flame retardant particle product.

[0024] The present invention also provides a method for preparing a fiber-reinforced composite environmentally friendly building formwork, comprising the following steps: S1. Add aerogel powder, polypropylene, cross-linking enhancer and auxiliary additives into a kneader, raise the temperature of the kneader to 115-125° C., knead for 5-10 minutes, add modified fiber and composite flame retardant particles into the kneader in sequence, knead for 15-25 minutes, add initiator into the kneader, knead for 40-60 minutes, granulate, and obtain a mixture; S2. Spread the mixed material flat on a flat vulcanizing machine, raise the temperature of the flat vulcanizing machine to 140-150°C, and the pressure to 12-16MPa. Keep the temperature and pressure for 40-60 minutes, and discharge the material after cooling to room temperature to obtain a building template. The present invention has the following beneficial effects: 1. The fiber-reinforced composite environmentally friendly building formwork of the present invention uses rice husks and straws as agricultural waste as raw materials, activates them and then performs surface modification treatment to prepare modified fibers. The reuse of the modified rice husks and straw fibers helps to reduce environmental pollution and waste of resources. The use of modified rice husks and straw fibers as part of the building formwork is in line with the concepts of green building and sustainable development. The modified fibers are reinforced with aerogel powders and composite flame-retardant particles as reinforcing materials to form a reinforcing system of aerogel powders, inorganic particles and fibers. Polypropylene and cross-linking reinforcing agents are used as organic adhesives. Under the action of an initiator, the cross-linking of molecular bonds between molecules of the building formwork is promoted to improve the overall mechanical properties of the building formwork. The fiber material is improved and then cooperated with the aerogel powders and composite flame-retardant particles to further improve the thermal insulation, flame retardant, water resistance and alkali resistance of the building formwork material.

[0025] 2. The fiber-reinforced composite environmentally friendly building formwork of the present invention can reduce the penetration and adsorption of water molecules and the water absorption and expansion of the fiber by modifying the fiber powder and treating the rice husk and straw fiber with surface modifiers such as KH-570 through activation treatment, thereby improving the interface compatibility between the fiber and the resin and making the two more closely combined; the aerogel powder has an extremely low density and high porosity, but its skeleton structure is extremely strong. When mixed with the modified fiber, the two can form complementary advantages to enhance the overall strength and rigidity of the building formwork. This enhanced mechanical property makes The obtained template can withstand a larger load and reduce deformation caused by external forces during use. In addition, aerogel micropowder has an extremely low thermal conductivity. After mixing it with modified fibers, it can significantly improve the thermal insulation properties of the building template. The high porosity and skeleton structure of diatomaceous earth in the composite flame retardant particles help to form an insulation barrier and reduce heat transfer. The silane compounds in the modification liquid may reduce the surface energy of diatomaceous earth through their unique chemical structure, such as fluorinated alkyl functional groups, which helps to reduce heat transfer on the surface of the material and the excellent waterproof performance of the inorganic particle surface, further improving the thermal insulation and waterproof properties of the material.

[0026] 3. The fiber-reinforced composite environmentally friendly building template of the present invention optimizes the raw material composition when preparing aerogel powder and composite flame-retardant particles, forms olefin double bond modification on the aerogel powder and the composite flame-retardant particles, and prepares triphenylthiophenol triazine with triphenylthiophenol modified triazine, which is further condensed with the alcohol hydroxyl group on 5-methyl-2-(1-methylvinyl)-4-hexene-1-ol to prepare a cross-linking enhancer with polyunsaturated olefin double bond modification, uses polypropylene as an organic binder, promotes the mixing of aerogel powder, modified fiber, and composite flame-retardant particles by a kneader, initiates a free radical polymerization reaction under the action of a free radical initiator, promotes mutual cross-linking between molecules in the building template, enhances the cohesion and structural stability of the building template material, and thus enhances the mechanical properties of the material, and the triazine structure introduced in the cross-linking enhancer is used as a nitrogen source, and the aluminum source in the aerogel powder and the phosphate in the composite flame-retardant particles are used as a phosphorus source to form a synergistic flame-retardant system in the building template, further improving the flame-retardant performance of the building template. DETAILED DESCRIPTION

[0027] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Example 1

[0029] This embodiment provides a method for preparing a fiber-reinforced composite environmentally friendly building formwork, comprising the following steps: S1. Preparation of cross-linking enhancer Weigh: 100 g of 4-aminobenzenethiol, 600 mL of anhydrous ethanol and 300 g of 30 wt% formaldehyde solution, add them into a reactor and stir, raise the temperature of the reactor to 60°C, keep the temperature for 6 hours, after the reaction is completed, keep the temperature of the reactor at 60°C, evaporate the solvent under reduced pressure, add 600 mL of dichloromethane and 100 mL of purified water into the reactor, stir for 20 minutes, stand for separation, dry the organic phase with anhydrous magnesium sulfate for 40 minutes, transfer it to a rotary evaporator with a water bath temperature of 40°C, evaporate dichloromethane under reduced pressure to obtain triphenylthiophenol triazine; Weigh: 41.2 g of triphenylthiophenol triazine, 66.7 g of isophorone diisocyanate and 333 mL of toluene, add them into a nitrogen-protected reactor and stir, raise the temperature of the reactor to 50°C, add 0.41 g of dibutyltin diacetate into the reactor, keep the temperature for 3 hours, add 5-methyl-2-(1-methylvinyl)-4-hexen-1-ol 50.5 g into the reactor, keep the temperature for 4 hours, after the reaction is completed, raise the temperature of the reactor to 70°C, evaporate toluene under reduced pressure to obtain a cross-linking enhancer.

[0030] S2, Aerogel powder Weigh: 30 g of aluminum sec-butoxide and 300 mL of isopropanol are added to the reactor and stirred until the system is dissolved. The temperature of the reactor is raised to 70°C, 50 mL of 0.8 mol / L dilute nitric acid is added to the reactor, and the reaction is kept warm for 2 hours. 80 g of tetraethyl orthosilicate and 20 g of allyltriethoxysilane are added to the reactor, and the mixture is stirred and kept warm for 2 hours. The mixture is allowed to stand and age for 8 hours. After the reaction is completed, the temperature of the reactor is kept at 70°C, the solvent is evaporated under reduced pressure, the temperature of the reactor is lowered to room temperature, 500 mL of anhydrous ethanol is added to the reactor, and the mixture is stirred and dispersed for 50 minutes. The mixture is allowed to stand and the supernatant is removed. The lower solid is centrifuged and dried, and then transferred to a drying oven at 60°C and dried to constant weight to obtain aerogel powder.

[0031] S3. Preparation of modified fiber Add rice husks and rice straw into a grinder and grind into fiber powder with a particle size of 5-8 mm; Mix potassium hydroxide, urea, sodium dodecyl sulfate, 10wt% hydrogen peroxide and purified water in a dosage ratio of 5g:2g:1g:30g:60mL to obtain an activation solution for later use; Weigh: 100 g of fiber powder and 1000 mL of activation solution are added to a reactor and stirred. The temperature of the reactor is raised to 70°C and kept warm for 2 hours. After the reaction is completed, the temperature of the reactor is lowered to room temperature, filtered, and the filter cake is washed with purified water until neutral and then dried. The filter cake is transferred to a drying oven at 60°C and dried to constant weight to obtain pretreated fiber; Weigh: 50 g of pretreated fiber, 500 g of anhydrous ethanol, and 20 g of KH-570, add them into the reactor and stir for 20 min, add 100 mL of 5 wt% sodium hydroxide solution into the reactor, raise the temperature of the reactor to 50 ° C, and keep it warm for 3 hours. After the reaction is completed, the temperature of the reactor is lowered to room temperature, filtered, and the filter cake is washed with purified water until it is neutral and then dried. The filter cake is transferred to a drying oven at a temperature of 60 ° C, dried to constant weight, and modified fiber is obtained.

[0032] S4. Preparation of composite flame retardant particles The diatomaceous earth is placed in a muffle furnace, the temperature of the muffle furnace is increased to 450°C, and the temperature is kept for 3 hours, and the temperature is naturally cooled to room temperature to obtain a calcined powder; Mixing tridecafluorooctyltrimethoxysilane and allyltriethoxysilane in a weight ratio of 2:1 to obtain a modification solution; Weigh: 100g of calcined powder and 200mL of 1.5mol / L phosphoric acid solution are added to a reactor and stirred. The temperature of the reactor is raised to 70°C and stirred for 30min. 100mL of 3.2mol / L urea solution is added to the reactor. The temperature of the reactor is raised to reflux and the reaction is carried out for 60min. 50g of the modification solution is added to the reactor. After the reaction is completed, the reactor is refluxed and the solution is evaporated under reduced pressure to obtain a crude composite flame retardant particle. The crude composite flame-retardant particles were transferred to a ball mill, the speed of the ball mill was set to 200 r / min, and the ball milling was performed for 30 minutes to obtain composite flame-retardant particles.

[0033] S5. Preparation of building formwork The antioxidant 168, sodium stearate, tributyl phosphate and dibutyl phthalate are uniformly mixed in a weight ratio of 1:2:3:2 to obtain an auxiliary additive; Weigh by weight: 30 parts of aerogel powder, 80 parts of polypropylene, 20 parts of cross-linking enhancer and 4 parts of auxiliary additives, add them into a kneader, raise the temperature of the kneader to 115°C, knead for 5 minutes, add 80 parts of modified fiber and 30 parts of composite flame retardant particles into the kneader in sequence, knead for 15 minutes, add 2 parts of benzoyl peroxide into the kneader, knead for 40 minutes, and granulate to obtain a mixture; The mixed material is spread flat on a flat plate vulcanizer, the temperature of the flat plate vulcanizer is increased to 140°C, the pressure is increased to 12MPa, and the heat and pressure are maintained for 40 minutes. After the mixture is cooled to room temperature, the material is discharged to obtain a building formwork.

[0034] Example 2

[0035] This embodiment provides a method for preparing a fiber-reinforced composite environmentally friendly building formwork, comprising the following steps: S1. Preparation of cross-linking enhancer Weigh: 100 g of 4-aminobenzenethiol, 600 mL of anhydrous ethanol and 400 g of 34 wt% formaldehyde solution, add them into a reactor and stir, raise the temperature of the reactor to 65°C, keep the temperature for 7 hours, after the reaction is completed, keep the temperature of the reactor at 65°C, evaporate the solvent under reduced pressure, add 600 mL of dichloromethane and 100 mL of purified water into the reactor, stir for 25 minutes, stand for separation, dry the organic phase with anhydrous magnesium sulfate for 50 minutes, transfer it to a rotary evaporator with a water bath temperature of 45°C, evaporate dichloromethane under reduced pressure to obtain triphenylthiophenol triazine; Weigh: 41.2 g of triphenylthiophenol triazine, 66.7 g of isophorone diisocyanate and 333 mL of toluene, add them into a nitrogen-protected reactor and stir, raise the temperature of the reactor to 55°C, add 0.41 g of dibutyltin diacetate to the reactor, keep the temperature for 3.5 hours, add 50.5 g of 5-methyl-2-(1-methylvinyl)-4-hexen-1-ol to the reactor, keep the temperature for 4.5 hours, after the reaction is completed, raise the temperature of the reactor to 75°C, evaporate toluene under reduced pressure to obtain a cross-linking enhancer.

[0036] S2, Aerogel powder Weigh: 40 g of aluminum sec-butoxide and 400 mL of isopropanol are added to the reactor and stirred until the system is dissolved. The temperature of the reactor is raised to 75°C, 60 mL of 1.0 mol / L dilute nitric acid is added to the reactor, and the reaction is kept warm for 2.5 hours. 90 g of tetraethyl orthosilicate and 25 g of allyltriethoxysilane are added to the reactor, and the mixture is stirred and kept warm for 2.5 hours. The mixture is allowed to stand for aging for 9 hours. After the reaction is completed, the temperature of the reactor is kept at 75°C, the solvent is evaporated under reduced pressure, the temperature of the reactor is lowered to room temperature, 500 mL of anhydrous ethanol is added to the reactor, and the mixture is stirred and dispersed for 55 minutes. The mixture is allowed to stand, and the supernatant is separated. The lower solid is centrifuged and dried, and then transferred to a drying oven at 65°C, and dried to constant weight to obtain aerogel powder.

[0037] S3. Preparation of modified fiber Add rice husks and rice straw into a grinder and grind into fiber powder with a particle size of 5-8 mm; Mix potassium hydroxide, urea, sodium dodecyl sulfate, 10wt% hydrogen peroxide and purified water in a dosage ratio of 5g:2g:1g:30g:60mL to obtain an activation solution for later use; Weigh: 100 g of fiber powder and 1250 mL of activation solution are added to a reactor and stirred. The temperature of the reactor is raised to 75°C and kept warm for 2.5 hours. After the reaction is completed, the temperature of the reactor is lowered to room temperature, filtered, and the filter cake is washed with purified water until neutral and then dried. The filter cake is transferred to a drying oven at a temperature of 65°C and dried to constant weight to obtain pretreated fiber; Weigh: 50 g of pretreated fiber, 500 g of anhydrous ethanol, and 25 g of KH-570, add them into the reactor and stir for 25 min, add 100 mL of 5 wt% sodium hydroxide solution into the reactor, raise the temperature of the reactor to 55 ° C, and keep it warm for 3.5 hours. After the reaction is completed, the temperature of the reactor is lowered to room temperature, filtered, and the filter cake is washed with purified water until it is neutral and then dried. The filter cake is transferred to a drying oven at a temperature of 65 ° C, dried to constant weight, and modified fiber is obtained.

[0038] S4. Preparation of composite flame retardant particles The diatomaceous earth was placed in a muffle furnace, the temperature of the muffle furnace was raised to 475°C, the temperature was kept for 3.5 hours, and the temperature was naturally lowered to room temperature to obtain a calcined powder; Mixing tridecafluorooctyltrimethoxysilane and allyltriethoxysilane in a weight ratio of 2:1 to obtain a modification solution; Weigh: 100g of calcined powder and 200mL of 1.5mol / L phosphoric acid solution are added to a reactor and stirred. The temperature of the reactor is raised to 75°C and stirred for 35min. 100mL of 3.2mol / L urea solution is added to the reactor. The temperature of the reactor is raised to reflux and the reaction is carried out for 70min. 50g of the modification solution is added to the reactor. After the reaction is completed, the reactor is refluxed and the solution is evaporated under reduced pressure to obtain a crude composite flame retardant particle. The crude composite flame retardant particles were transferred to a ball mill, the speed of the ball mill was set to 225 r / min, and the ball milling was performed for 35 minutes to obtain composite flame retardant particles.

[0039] S5. Preparation of building formwork The antioxidant 1010, calcium stearate, tri(2-ethylhexyl) phosphate and dioctyl phthalate are uniformly mixed in a weight ratio of 1:2:3:2 to obtain an auxiliary additive; Weigh by weight: 40 parts of aerogel powder, 90 parts of polypropylene, 25 parts of cross-linking enhancer and 5 parts of auxiliary additives, add them into a kneader, raise the temperature of the kneader to 120°C, knead for 8 minutes, add 90 parts of modified fiber and 35 parts of composite flame retardant particles into the kneader in sequence, knead for 20 minutes, add 2.5 parts of benzoyl peroxide into the kneader, knead for 50 minutes, and granulate to obtain a mixture; The mixed material was spread evenly in a flat vulcanizing press, the temperature of the press was raised to 145°C, the pressure was raised to 14MPa, and the press was kept warm and pressure maintained for 50 minutes. After the mixture was cooled to room temperature, the material was discharged to obtain a building formwork.

[0040] Example 3

[0041] This embodiment provides a method for preparing a fiber-reinforced composite environmentally friendly building formwork, comprising the following steps: S1. Preparation of cross-linking enhancer Weigh: 100 g of 4-aminobenzenethiol, 600 mL of anhydrous ethanol and 500 g of 37 wt% formaldehyde solution, add them into a reactor and stir, raise the temperature of the reactor to 70°C, keep the temperature for reaction for 8 hours, after the reaction is completed, keep the temperature of the reactor at 70°C, evaporate the solvent under reduced pressure, add 600 mL of dichloromethane and 100 mL of purified water into the reactor, stir for 30 minutes, stand for separation, dry the organic phase with anhydrous magnesium sulfate for 60 minutes, transfer it to a rotary evaporator with a water bath temperature of 50°C, evaporate the dichloromethane under reduced pressure to obtain triphenylthiophenol triazine; Weigh: 41.2 g of triphenylthiophenol triazine, 66.7 g of isophorone diisocyanate and 333 mL of toluene, add them into a nitrogen-protected reactor and stir, raise the temperature of the reactor to 60°C, add 0.41 g of dibutyltin diacetate into the reactor, keep the temperature for 4 hours, add 50.5 g of 5-methyl-2-(1-methylvinyl)-4-hexen-1-ol into the reactor, keep the temperature for 5 hours, after the reaction is completed, raise the temperature of the reactor to 80°C, evaporate toluene under reduced pressure to obtain a cross-linking enhancer.

[0042] S2, Aerogel powder Weigh: 50 g of aluminum sec-butoxide and 3500 mL of isopropanol are added to the reactor and stirred until the system is dissolved. The temperature of the reactor is raised to 80°C, 70 mL of 1.3 mol / L dilute nitric acid is added to the reactor, and the reaction is kept warm for 3 hours. 100 g of ethyl orthosilicate and 30 g of allyltriethoxysilane are added to the reactor, and the mixture is stirred and kept warm for 3 hours. The mixture is allowed to stand for aging for 10 hours. After the reaction is completed, the temperature of the reactor is kept at 80°C, the solvent is evaporated under reduced pressure, the temperature of the reactor is lowered to room temperature, 500 mL of anhydrous ethanol is added to the reactor, and the mixture is stirred and dispersed for 60 minutes. The mixture is allowed to stand, and the supernatant is separated. The lower solid is centrifuged and dried, and then transferred to a drying oven at 70°C and dried to constant weight to obtain aerogel powder.

[0043] S3. Preparation of modified fiber Add rice husks and rice straw into a grinder and grind into fiber powder with a particle size of 5-8 mm; Mix potassium hydroxide, urea, sodium dodecyl sulfate, 10wt% hydrogen peroxide and purified water in a dosage ratio of 5g:2g:1g:30g:60mL to obtain an activation solution for later use; Weigh: 100 g of fiber powder and 1500 mL of activation solution are added to a reactor and stirred. The temperature of the reactor is raised to 80°C and kept warm for 3 hours. After the reaction is completed, the temperature of the reactor is lowered to room temperature, filtered, and the filter cake is washed with purified water until neutral and then dried. The filter cake is transferred to a drying oven at 70°C and dried to constant weight to obtain pretreated fiber; Weigh: 50 g of pretreated fiber, 500 g of anhydrous ethanol, and 30 g of KH-570, add them into the reactor and stir for 30 min, add 100 mL of 5 wt% sodium hydroxide solution into the reactor, raise the temperature of the reactor to 60 ° C, and keep it warm for 4 hours. After the reaction is completed, the temperature of the reactor is lowered to room temperature, filtered, and the filter cake is washed with purified water until it is neutral and then dried. The filter cake is transferred to a drying oven at a temperature of 70 ° C, dried to constant weight, and modified fiber is obtained.

[0044] S4. Preparation of composite flame retardant particles The diatomaceous earth is placed in a muffle furnace, the temperature of the muffle furnace is increased to 500°C, the temperature is kept for 4 hours, and the temperature is naturally lowered to room temperature to obtain a calcined powder; Mixing tridecafluorooctyltrimethoxysilane and allyltriethoxysilane in a weight ratio of 2:1 to obtain a modification solution; Weigh: 100g of calcined powder and 200mL of 1.5mol / L phosphoric acid solution are added to a reactor and stirred. The temperature of the reactor is raised to 80°C and stirred for 40min. 100mL of 3.2mol / L urea solution is added to the reactor. The temperature of the reactor is raised to reflux and the reaction is carried out for 80min. 50g of the modification solution is added to the reactor. After the reaction is completed, the reactor is refluxed and the solution is evaporated under reduced pressure to obtain a crude composite flame retardant particle. The crude composite flame-retardant particles were transferred to a ball mill, the speed of the ball mill was set to 250 r / min, and the ball milling was performed for 40 minutes to obtain composite flame-retardant particles.

[0045] S5. Preparation of building formwork The antioxidant 1076, zinc stearate, tris(2,3-dichloropropyl) phosphate and dipropyl phthalate are uniformly mixed in a weight ratio of 1:2:3:2 to obtain an auxiliary additive; Weigh by weight: 50 parts of aerogel powder, 100 parts of polypropylene, 30 parts of cross-linking enhancer and 6 parts of auxiliary additives, add them into a kneader, raise the temperature of the kneader to 125°C, knead for 10 minutes, add 100 parts of modified fiber and 40 parts of composite flame retardant particles into the kneader in sequence, knead for 25 minutes, add 3 parts of benzoyl peroxide into the kneader, knead for 60 minutes, and granulate to obtain a mixture; The mixed material is spread flat on a flat plate vulcanizer, the temperature of the flat plate vulcanizer is increased to 150°C, the pressure is increased to 16MPa, and the heat and pressure are maintained for 60 minutes. After the mixture is cooled to room temperature, it is discharged to obtain a building formwork.

[0046] Comparative Example 1 The difference between this comparative example and Example 3 is that in step S1, 1,3,5-cyclohexanetriol is used in an equal molar amount to replace triphenylthiophenol triazine to participate in the preparation of the cross-linking enhancer.

[0047] Comparative Example 2 The difference between this comparative example and Example 3 is that in step S2, aluminum sec-butoxide is not added.

[0048] Comparative Example 3 The difference between this comparative example and Example 3 is that step S3 is eliminated, and the fiber powder in step S3 replaces the modified fiber in step S5.

[0049] Comparative Example 4 The difference between this comparative example and Example 3 is that in step S4, no modification liquid is added.

[0050] Performance Testing: The mechanical properties, flame retardant properties and thermal insulation properties of the building formwork prepared in Examples 1-3 and Comparative Examples 1-4 were tested. The mechanical properties were measured by referring to the standard GB / T 29500-2013 "Wood-Plastic Composite Panels for Building Formwork" to measure the static bending strength, simply supported beam impact strength, alkali resistance and water absorption of the sample. The flame retardant properties were measured by referring to the standard GB 8624-2012 "Classification of Combustion Performance of Building Materials and Products" to measure the combustion performance grade of the sample. The thermal insulation properties were measured by referring to the standard GB / T 32064-2015 "Test Method for Thermal Conductivity and Thermal Diffusivity of Building Materials by Transient Plane Heat Source". The specific test results are shown in Table 1-2: Table 1-Mechanical properties test data of the sample Category Static bending strength / MPa <![CDATA[Izod impact strength / kJ·m -2 > Water absorption / % Alkali resistance Example 1 51.3 17.5 0.231 No bubbles or cracks on the surface Example 2 52.1 17.8 0.214 No bubbles or cracks on the surface Example 3 51.8 17.4 0.223 No bubbles or cracks on the surface Comparative Example 1 50.3 17.1 0.228 No bubbles or cracks on the surface Comparative Example 2 50.7 17.3 0.225 No bubbles or cracks on the surface Comparative Example 3 43.6 15.2 0.487 The surface is slightly bubbling and cracked Comparative Example 4 49.6 16.7 0.311 The surface is slightly bubbling and has no cracks Table 2- Flame retardant and thermal insulation performance test data of the samples Category Combustion performance grade / level <![CDATA[Thermal conductivity / W·(m·K) -1 > Example 1 A2 0.15 Example 2 A2 0.12 Example 3 A2 0.14 Comparative Example 1 B 0.17 Comparative Example 2 B 0.21 Comparative Example 3 A2 0.35 Comparative Example 4 A2 0.17 Data Analysis: Comparing and analyzing the data in Table 1-2 above, the static bending strength of the building template material prepared in the present invention reaches 52.1MPa, and the simply supported beam impact strength reaches 17.8kJ / m 2 , the water absorption rate is reduced to 0.214%, the combustion performance level reaches A2, the thermal conductivity is reduced to 0.12W / (m·K), and the building formwork has good alkali resistance, and all performance parameters are better than the control example; It is explained that the present invention recycles rice husks and straws as reinforcing fibers, which helps to reduce environmental pollution and waste of resources, conforms to the concepts of green building and sustainable development, and uses aerogel micropowder and composite flame retardant particles as reinforcing materials to reinforce the modified fibers, and uses polypropylene and cross-linking enhancers as organic adhesives. Under the action of an initiator, the cross-linking bonds between the molecules of the building formwork are promoted, which not only improves the overall mechanical properties of the building formwork, but also further improves the thermal insulation, flame retardant, water resistance and alkali resistance of the building formwork material.

[0051] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

[0052] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0053] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A fiber-reinforced composite environmentally friendly building formwork, It is characterized in that The invention comprises the following components in parts by weight: 80-100 parts of polypropylene, 20-30 parts of a cross-linking enhancer, 30-50 parts of aerogel powder, 80-100 parts of modified fiber, 30-40 parts of composite flame retardant particles, 2-3 parts of an initiator and 4-6 parts of an auxiliary additive; The cross-linking enhancer is obtained by processing the following steps: A1, adding 4-aminobenzenethiol, anhydrous ethanol and formaldehyde solution into a reaction kettle and stirring, raising the temperature of the reaction kettle to 60-70°C, keeping the temperature for reaction for 6-8h, and post-treating to obtain triphenylthiophenol triazine; A2. Add triphenylthiophenol triazine, isophorone diisocyanate and toluene into a nitrogen-protected reactor and stir. The temperature of the reactor is raised to 50-60° C., a catalyst is added into the reactor, and the reaction is kept warm for 3-4 hours. Add 5-methyl-2-(1-methylvinyl)-4-hexen-1-ol into the reactor, and the reaction is kept warm for 4-5 hours. Post-treatment is performed to obtain a cross-linking enhancer.

2. A fiber-reinforced composite environmentally friendly building formwork according to claim 1, It is characterized in that The initiator is benzoyl peroxide, the auxiliary additives are composed of an antioxidant, a dispersant, a flame retardant and a plasticizer in a weight ratio of 1:2:3:2, the antioxidant is one or more of antioxidant 168, antioxidant 1010, and antioxidant 1076, the dispersant is one or more of sodium stearate, calcium stearate, zinc stearate, and magnesium stearate, the flame retardant is one or more of tributyl phosphate, tri(2-ethylhexyl) phosphate, tri(2-chloroethyl) phosphate, tri(2,3-dichloropropyl) phosphate, and tri(2,3-dibromopropyl) phosphate, and the plasticizer is a phthalate.

3. A fiber-reinforced composite environmentally friendly building formwork according to claim 1, It is characterized in that In step A1, the amount ratio of 4-aminobenzenethiol, anhydrous ethanol and formaldehyde solution is 1g:6mL:3-5g, and the mass fraction of the formaldehyde solution is 30-37%; in step A2, the molar ratio of triphenylthiophenol triazine, isophorone diisocyanate and 5-methyl-2-(1-methylvinyl)-4-hexene-1-ol is 1:3:3, and the amount ratio of isophorone diisocyanate, toluene and catalyst is 1g:5mL: 0.01 g, the catalyst is dibutyltin diacetate.

4. A fiber-reinforced composite environmentally friendly building formwork according to claim 1, It is characterized in that The preparation method of the aerogel micropowder is as follows: adding aluminum sec-butoxide and isopropanol into a reaction kettle and stirring until the system is dissolved, raising the temperature of the reaction kettle to 70-80° C., adding dilute nitric acid into the reaction kettle, keeping the temperature for reaction for 2-3 hours, adding ethyl orthosilicate and allyltriethoxysilane into the reaction kettle, keeping the temperature for reaction for 2-3 hours, standing for aging for 8-10 hours, and post-treating to obtain the aerogel micropowder.

5. A fiber-reinforced composite environmentally friendly building formwork according to claim 4, It is characterized in that The dosage ratio of the aluminum sec-butoxide, isopropanol, dilute nitric acid, ethyl orthosilicate and allyltriethoxysilane is 3-5g:30-50mL:5-7mL:8-10g:2-3g, and the concentration of the dilute nitric acid is 0.8-1.3mol / L.

6. A fiber-reinforced composite environmentally friendly building formwork according to claim 1, It is characterized in that The modified fiber is obtained by processing the following steps: B1. Add rice husk and rice straw into a grinder and grind into fiber powder with a particle size of 5-8 mm; B2, adding fiber powder and activation solution into the reactor and stirring, raising the temperature of the reactor to 70-80°C, keeping the temperature for reaction for 2-3h, and post-treating to obtain pretreated fiber; B3. Add the pretreated fiber, anhydrous ethanol and KH-570 into the reactor and stir for 20-30 minutes. Add 5wt% sodium hydroxide solution into the reactor, increase the temperature of the reactor to 50-60°C, keep the temperature for 3-4 hours, and obtain the modified fiber after post-treatment.

7. A fiber-reinforced composite environmentally friendly building formwork according to claim 6, It is characterized in that In step B2, the fiber powder and activation solution are used in a ratio of 1g:10-15mL, and the activation solution is composed of potassium hydroxide, urea, sodium dodecyl sulfate, 10wt% hydrogen peroxide and purified water in a ratio of 5g:2g:1g:30g:60mL; in step B3, the pretreated fiber, anhydrous ethanol, KH-570 and 5wt% sodium hydroxide solution are used in a ratio of 5g:50mL:2-3g:10mL.

8. The fiber-reinforced composite environmentally friendly building formwork according to claim 1, It is characterized in that The composite flame retardant particles are processed by the following steps: C1. Place diatomaceous earth in a muffle furnace, raise the temperature of the muffle furnace to 450-500°C, keep the temperature for 3-4 hours, and naturally cool to room temperature to obtain a calcined powder; C2, adding the calcined powder and phosphoric acid solution into the reactor and stirring, raising the temperature of the reactor to 70-80°C, keeping warm and stirring for 30-40 minutes, adding urea solution into the reactor, raising the temperature of the reactor to reflux the system, keeping warm and reacting for 60-80 minutes, adding the modification liquid into the reactor, and post-treating to obtain the crude composite flame retardant particles; C3. Transfer the crude composite flame-retardant particles to a ball mill, set the speed of the ball mill to 200-250 r / min, and ball mill for 30-40 min to obtain composite flame-retardant particles.

9. A fiber-reinforced composite environmentally friendly building formwork according to claim 1, It is characterized in that In step C2, the amount ratio of the calcined powder, the phosphoric acid solution, the urea solution and the modifying solution is 10g:20mL:10mL:5g, the concentration of the phosphoric acid solution is 1.5mol / L, the concentration of the urea is 3.2mol / L, and the modifying solution is composed of tridecafluorooctyltrimethoxysilane and allyltriethoxysilane in a weight ratio of 2:

1.

10. A method for preparing a fiber-reinforced composite environmentally friendly building formwork, applicable to a fiber-reinforced composite environmentally friendly building formwork as claimed in any one of claims 1 to 9, It is characterized in that The following steps are involved: S1. Add aerogel powder, polypropylene, cross-linking enhancer and auxiliary additives into a kneader, raise the temperature of the kneader to 115-125° C., knead for 5-10 minutes, add modified fiber and composite flame retardant particles into the kneader in sequence, knead for 15-25 minutes, add initiator into the kneader, knead for 40-60 minutes, granulate, and obtain a mixture; S2. Spread the mixed material evenly in a flat vulcanizing machine, increase the temperature of the flat vulcanizing machine to 140-150°C, increase the pressure to 12-16MPa, keep the temperature and pressure for 40-60 minutes, and discharge the material after naturally cooling to room temperature to obtain a building formwork.

Citation Information

Patent Citations

  • Hemp fiber and preparation method thereof

    CN101831715A

  • Preparation method of high temperature-resistant alumina aerogel material

    CN103342537A

  • Decorative plate and manufacturing method thereof

    CN112140275A

  • Preparation method of high-temperature-resistant silicon-modified alumina aerogel

    CN113683110A

  • Processing method of high-toughness MPP electric power pipe

    CN117402429A

Cited By

  • Preparation and resource utilization method of aerogel thermal insulation material based on ardealite slag solid waste

    CN120841927A